2023
DOI: 10.3390/antibiotics12020402
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Virulence and Antibiotic Resistance in Campylobacter spp. Livestock Isolates

Abstract: Campylobacter remains the most prevalent foodborne pathogen bacterium responsible for causing gastroenteritis worldwide. Specifically, this pathogen colonises a ubiquitous range of environments, from poultry, companion pets and livestock animals to humans. The bacterium is uniquely adaptable to various niches, leading to complicated gastroenteritis and, in some cases, difficult to treat due to elevated resistance to certain antibiotics. This increased resistance is currently detected via genomic, clinical or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 109 publications
0
26
0
Order By: Relevance
“…The mechanisms of antibiotic resistance in Campylobacter have been widely studied. However, the pathogenic mechanisms and the mode of interaction of Campylobacter with the host are not fully defined (12,48). A prevalence of 21% was detected for the wlaN and cstIII genes, with a possible association with ST-50 because these two genes were detected in 80% of the isolates belonging to ST-50 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of antibiotic resistance in Campylobacter have been widely studied. However, the pathogenic mechanisms and the mode of interaction of Campylobacter with the host are not fully defined (12,48). A prevalence of 21% was detected for the wlaN and cstIII genes, with a possible association with ST-50 because these two genes were detected in 80% of the isolates belonging to ST-50 (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the pathogenicity and virulence of C. jejuni are not fully understood. However, several genes involved in motility, cell cytotoxicity, invasion, chemotaxis, and the cellular stress response have been described (12)(13)(14). Virulence factors (wlaN, cgtB, cstII, and cstIII) implicated in the pathogenesis of GBS via the modification of lipooligosaccharide (LOS) have also been studied (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…As a commensal organism with high load (10 9 CFU/g) in chicken ceca, Campylobacter easily contaminates carcasses of slaughtered birds (Thibodeau et al, 2015) . With the widespread use of antimicrobial agents in poultry and livestock production systems, the surveillance of AMR in Campylobacter has identified high levels of resistance to some drugs in many parts of the world (Bundurus et al, 2023) . Furthermore, severe MDR increases the threat to public safety ( Zhang et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, Bacillus causes cutaneous, abdominal, or gastrointestinal anthrax in humans and reared livestock 40 . Campylobacter causes reproductive and intestinal infections in livestock and poultry, and may also cause abortion and infertile fetuses in cattle and sheep; it can also infect humans, causing miscarriage, premature births, septicemia, and similar symptoms 42,43 . It has been demonstrated that domestic animals serve as the largest potential reservoir of zoonotic viral diseases 44 .…”
Section: Composition Of Pathogenic Bacteria and Fungi In Bioaerosols ...mentioning
confidence: 99%